Wild tribes and ancient Semites: Israelite-Indian identification and the American West - Imhoff, Sarah (Culture and religion, 2014)
Rabbi Henry Cohen of Galveston, Texas, carefully preserved a 1916 pamphlet that claimed a common history for 'Wild tribes' of Indians and Jews of antiquity. Why would a Jewish author tie the customs of 'uncivilised' tribes to his own religion, and why might it capture Cohen's attention? This article suggests that the 'Indian-Israelite' identification appealed to acculturated Jews like Cohen as part of a wider embrace of a vision of manhood that at once held ties to Jewishness and American identity. That is, identification with the American West and frontier emphasised the harmony between Jewishness, a particular type of enlightened Judaism, and Americanisation. A brief survey of three movements - the relatively small-scale Galveston Movement, Jewish agricultural communities and the larger, more diverse Zionist movement - then demonstrates how the gendered and nationalist ideologies of Henry Cohen and other acculturated Jews like him aligned with their imagined constructions of Indians.